Ecological Perspectives in Language Education: A Critical Look at ELT Practices in Higher Education - Rizal, Rizka Patrika; Seli, Fenny Yutika (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2025)
As global environmental challenges intensify, integrating green ecoliteracy into higher education has become increasingly relevant, including within English Language Teaching (ELT). This study explores how ecoliteracy is represented and practiced in ELT curricula at the tertiary level, focusing on syllabi, textbooks, and educator perspectives. Employing a qualitative research design, the study combines content analysis of three ELT syllabi and textbooks with semi-structured interviews involving two lecturers and a program coordinator at a private university. The results reveal that while environmental themes occasionally appear in course materials, their integration is often incidental, fragmented, and lacks critical engagement. Institutional and pedagogical barriers—such as limited curriculum guidelines, insufficient teacher training, and a dependence on commercial textbooks—hamper the effective inclusion of ecoliteracy. Nevertheless, there is growing awareness among educators of the potential value in embedding sustainability themes to promote critical thinking, global citizenship, and interdisciplinary learning. This study underscores the need for structured, localized, and critically designed materials and professional development initiatives to support the meaningful inclusion of green ecoliteracy in ELT at the higher education level.